Operating Rules - McGill Community For Lifelong Learning (MCLL) (2022)

The Newsletter : Fall 2018: Volume 29, No. 3 - McGill Community For Lifelong Learning (MCLL) (2018)
Number of pages: 12

The Newsletter : Spring 2019: Volume 30, No. 2 - McGill Community For Lifelong Learning (MCLL) (2019)
Number of pages: 8

The Newsletter : Winter 2019: Volume 30, No. 1 - McGill Community For Lifelong Learning (MCLL) (2019)
Number of pages: 12

The Newsletter : Fall 2020: Volume 31, No. 2 - McGill Community For Lifelong Learning (MCLL) (2020)
Number of pages: 12

Fall 2022 : MCLL News - McGill Community For Lifelong Learning (MCLL) (2022)
Number of pages: 12

Annual Report : 2020-2021 - McGill Community For Lifelong Learning (MCLL) (2021)

Moderators’ Handbook : September 2019 - McGill Community For Lifelong Learning (MCLL) (2019)

Report of the Planning Committee on the 2018 Members’ Forum - McGill Community For Lifelong Learning (MCLL) (2018)
A Members’ Forum was held on 26 October 2018 to discuss the issue of peer learning at MCLL. The three major findings and the four recommendations are presented here

Survey of MCLL Moderator Engagement : Report to the MCLL Council - McGill Community For Lifelong Learning (MCLL) (2021)
In December 2019, Council requested that the Planning Committee create and administer a survey of moderators to inquire about their engagement in the MCLL community in the service of retaining and recruiting moderators. Due to the COVID-19 outbreak and the high-priority burden the pandemic put on various committees, the survey was delayed until late in the Fall 2020 term. This document reports on the survey results and includes, in appendices, the survey questions as well as the detailed results including all comments received by respondents.

November 2022 eBulletin - McGill Community For Lifelong Learning (MCLL) (2022)
Number of pages: 7

October 2021 eBulletin - McGill Community For Lifelong Learning (MCLL) (2022)
Number of pages: 3

September 2022 eBulletin - McGill Community For Lifelong Learning (MCLL) (2022)
Number of pages: 6

McGill Community for Lifelong Learning : Elected Council Members and Committee Chairs - McGill Community For Lifelong Learning (MCLL) (2019)

McGill Community for Lifelong Learning : Operating Rules - McGill Community For Lifelong Learning (MCLL) (2014)